Dinamika Pengembangan Kurikulum Pendidikan Agama Islam di Madrasah (Studi Multi-Situs di Kabupaten Jombang) - Umam, Khoirul (Jurnal Pendidikan Agama Islam (Journal of Islamic Education Studies), 2018)
In the dynamic context of curriculum development in Indonesia, Islamic education subject encounters various problems in its curriculum development. This is caused by difference in school ownership status, school environment, and the availability of human resources. This research proposes to analyze problems in the implementation of curriculum development, curriculum construction, and factors supporting and preventing curriculum development in MTs Salafiyah Syafi’iyah Tebuireng, MTs Ar-Rahman Nglaban, MTsN Plandi Diwek, and MTsN Tambakberas Jombang. This research makes use field research approach with multi-sites within four madrasah in Jombang Regency. Results show that the four madrasah put too much attention to subject centered design. Human resources and infrastructure become dominant determining factors. Material essence and quality become distinguishing factors after the comparation. From data collected in the four madrasah, collaborative curriculum may be an ideal and applicable alternative in redesigning curriculum.